KEDUDUKAN HUKUM ANAK ANGKAT DALAM HUKUM ISLAM DAN HUKUM ADAT DI INDONESIA - Junaidi Junaidi (Universitas Sebelas Maret, 2016)
The purpose of this study is to know differences in the basic concepts related to child adoption in Islamic Law and Customary Law. The method used is a normative legal research or doctrinal. Adoption has happened very long with a variety of backgrounds and objectives. Adoption will cause the rights and obligations for the child and the adoptive parents. In Islamic law adoption is prohibited when the position adopted child the same as biological children, but advocated the adoption of Islamic law in the sense of the maintenance of the child. In indigenous communities, the concept of adoption is no uniformity. In general adoption will lead to an adopted child will have a stronger relationship with his adoptive parents, even in some ethnic groups, children raised disconnected relationship with the biological parent.Keywords: Adoption, Islamic Law, Customary Law